ANALISIS ANGGARAN PENDAPATAN DAN BELANJA DAERAH PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KOTA MEDAN - Nasution, Nina Andriany (AKTUAL, 2023)
This study aims to compile a Budget Realization Report (LRA) in which there is a ratio with the criteria. The theory used in this research is government accounting standards and the hypothesis proposed is that the variance of APBD income is not good, regional self-reliance is very good, the effectiveness of PAD is quite effective, the variance of APBD spending is profitable and the efficiency of Regional Expenditure. That the analytical tool in this research uses quantitative descriptive method, namely by studying government accounting standards applied in the field so that there is a difference with phenomena and fields in the field of Regional Finance and Assets Medan City Management Board (BPKAD). Based on the research results, you can concluded that regional revenues have not been able to be obtained income exceeds the budgeted amount and has not been able to afford increase regional original income including its receipts. While regional spending is for operational spending and capital expenditure to total regional expenditure has not fully able to improve alignment with the total regional spending. Â  Â 